PENGARUH MODEL INQUIRY LEARNING DAN DIRECT INSTRUCTION DALAM PENDIDIKAN JASMANI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH MENENGAH PERTAMA - Prasetyo, Eko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2017)
This study aims to determine the effect between instructional model Inquiry Learning and Direct Instruction to critical thinking skills of Junior High School children in accordance with gender differences between men and women. The method used in this research is to use the experimental method using a quantitative approach with the type of case study. In this study, the measurement tool is a questionnaire that the author quotes from the questionnaire Bambang Abduljabar. The results of this study are: Inquiry learning model in learning pemas can improve students' critical thinking skills without feared will be influenced by sex differences in students. The more student-centered learning of lead will contribute positively to the students' cognitive development, even giving the student a pleasurable learning experience.